Association between receiving the Aksi Bergizi Social Behavioral Change Communication (SBCC) intervention and dietary habits among secondary school students in Padang, Indonesia - Ricvan Dana Nindrea; Sawitri Assanangkornchai; Masrul Muchtar; Virasakdi Chongsuvivatwong; Wit Wichaidit (PLoS ONE, 2025)
Background The Government of Indonesia and UNICEF introduced the Aksi Bergizi Social Behavioral Change Communication (SBCC) intervention to promote healthy dietary behaviors among adolescents. However, no systematic assessment of the Program’s effect has been made. The objectives of this study are: 1) to assess the extent to which exposure to the Aksi Bergizi Program is associated with dietary behaviors among secondary school students, and; 2) to assess mediation of the mentioned association by dietary self-efficacy. Methods We conducted a school-based cross-sectional study in Padang Municipality, Indonesia. We collected data from 253 students attending Aksi Bergizi target schools, and 253 students from non-target schools, using self-administered questionnaire with a food frequency questionnaire (FFQ) section. We analyzed data using descriptive statistics with analysis of mediation by self-efficacy in dietary consumption. Results We identified three distinct dietary patterns among the students: one characterized by higher frequencies of eating meat, processed foods, and dessert (i.e., “High Protein and Processed Foods” dietary pattern), another by higher frequencies of eating snacks and sweetened drinks (“Snacks and Sugary Drinks”), and another by higher frequencies of eating soybean products and fresh fruits and lower frequency of eating preserved vegetables (“Healthier Diet”). Students in the Aksi Bergizi target schools were significantly less likely than students in the non-target schools to have the High Protein and Processed Foods dietary pattern (40.2% vs. 53.9%, Adjusted OR = 0.44; 95% CI = 0.20, 0.99) and more likely to have a Healthier Diet pattern, although the difference of the latter was not statistically significant. Students in the target schools, however, were also more likely than students in the non-target schools to have the Snacks and Sugary Drinks dietary pattern (78.7% vs. 40.4%, Adjusted OR = 6.22; 95% CI = 2.68, 14.42). Regarding mediation, students in the Aksi Bergizi target schools had significantly different dietary self-efficacy from students in the non-target schools (p < 0.001). However, self-efficacy was not significantly associated with dietary habits. The association in the non-mediated pathway between exposure to the Aksi Bergizi program and dietary habits was statistically significant (p < 0.001). Conclusion The findings of this study have implications for stakeholders in adolescent health. However, limitations regarding the cross-sectional design (which precludes the ability to make causal inference), social desirability, and limited generalizability should be considered in the interpretation of the study findings.